Diagnoses of sexual abuse and their common registered comorbidities in the total population of Stockholm. Issue 6 (11th January 2017) - Rajan, Gita; Ljunggren, Gunnar; Wändell, Per; Wahlström, Lars; Svedin, Carl-Göran; Carlsson, Axel C
Abstract : Background: Prior research based on self-reports has proven sexual abuse to be a risk factor for pain and psychiatric disorders. However, less is known about how this is reflected within the healthcare system. The aim of this study was to study the 2-year prevalence of diagnosis of sexual abuse and concomitant conditions. Methods: Using data from VAL, the study population included all living persons in Stockholm County, Sweden, between 1 January 2008 and 31 December 2014 (N=2 549 496). Diagnoses of sexual abuse were identified during 2013–2014, with information on the concomitant conditions somatic pain, depression, anxiety, psychotic disorders and bipolar disorders, stress disorders and alcohol and substance abuse. All diagnoses were prospectively registered. Age and neighbourhood socioeconomic status-adjusted ORs with 95% CIs for individuals with a diagnosis of sexual abuse, using individuals without sexual abuse as referents, were calculated. Results: Girls at the ages 13–17 years had the highest 2-year prevalence (0.69%) of sexual abuse followed by girls 5–12 years (0.11%), and girls 0–4 years (0.04%). For women 45 years and older the 2-year prevalence rates were substantially lower (0.008–0.004%). The highest 2-year prevalence of sexual abuse in men was seen in boys 5–12 (0.03%) years. The total 2-year prevalence of diagnoses of sexual abuse among the population in the material was 0.04%. The highest ORs of comorbidities for girls (ages 0–17 years) with sexual abuse versus those without sexual abuse were: Stress disorder; 15.7 (13.1 to 18.9), drug abuse; 10.0 (7.7 to 13.0), and alcohol abuse; 9.7(7.8 to 12.0). For boys (ages 0–17 years), the highest ORs of comorbidities were: Stress disorder 12.4 (6.0 to 25.7), anxiety disorders; 5.5 (2.6 to 11.5), and alcohol abuse; 3.9 (1.4 to 11.3). The highest ORs of comorbidities for women (18–) with sexual abuse versus those without sexual abuse were: alcohol abuse; 19.3 (12.6 to 29.6), drug abuse; 16.7 (10.7 to 26.1) and psychotic disorders; 15.3 (8.0 to 29.4). For men (18–) the highest ORs of comorbidities were: alcohol abuse; 25.8 (15.2 to 43.9), anxiety disorders; 14.3 (8.5 to 24.2) stress disorder; 12.9 (7.5 to 22.1) and drug abuse; 12.9 (6.9 to 24.1). Conclusions: Diagnoses of drug and alcohol abuse, psychotic, bipolar, stress anxiety disorders, depression and somatic pain are more common among individuals with a diagnosis of sexual abuse than among individuals without a diagnosis of sexual abuse.